PENGARUH KECAKAPAN MANAJERIAL DAN STRUKTUR MODAL PADA KINERJA DAN NILAI PERUSAHAAN - Nadia Damayanti; Imam Subekti (Jurnal Ilmiah Mahasiswa FEB, 2014)
This research aims to examine the effect of managerial ability and capital structure on firm performance and firm value, with firm size and firm growth as control variable. Research samples were manufacturing  companies   listed on Indonesia Stock Exchange (IDX)  at 2011, 2012, and  2013. This research used Data Envelopment Analysis (DEA) to measure managerial ability, and capital structure were measured by DER. The results of this research showed that more skilled  manager will inrease firm performance as measured by ROA and firm value as measured by share price. Another result shows that higher rate of DER will decrease firm performance as measured by ROA and firm value as measured by share price. Control variable firm size is proved to have significant positive effect on ROA and share price. Firm growth has significant positive effect on ROA, but has no effect on share price.Keywords: Managerial Ability, Capital Structure, Data Envelopment Analysis, Firm Performance, Firm Value, Firm Size, Firm Growth.